Hydrogen supplement co-combustion with diesel in compression ignition engine. (October 2015) - Hamdan, Mohammad O.; Selim, Mohamed Y.E.; Al-Omari, Salah-A.B.; Elnajjar, Emad
Abstract: The present work investigates experimentally the behavior of compression ignition engine while boosting the combustion by enriching air-intake manifold with hydrogen supplement at the atmospheric condition. The study reports the engine thermal efficiency, NO x emissions and engine exhaust temperature while varying hydrogen content, engine speed and ignition timing. The results show that thermal efficiency of the compression ignition engine increases as hydrogen content increases in the air-intake manifold for the same diesel mass flow rate. The effect of hydrogen supplement on engine efficiency is more pronounced at low engine speed and part-load. The hydrogen supplement causes an increase in NO x emissions which is attributed to the increase in the combustion temperature and as a result, lower smoke opacity numbers are attained. Highlights: Hydrogen is introduced to diesel engine at atmosphere condition through air intake manifold with no major engine retrofit. The hydrogen supplement enhances diesel engine thermal efficiency. The hydrogen that is produced from solar energy and water electrolysis can be used to reduce diesel fuel consumption. The hydrogen supplement enhances combustion since it has high heating value and high adiabatic flame temperature. The use of hydrogen reduces PM emission but increases NOx emission.